1986
DOI: 10.1152/jappl.1986.61.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lung volume on oxygen cost of resistive breathing

Abstract: We examined the relationship between the O2 cost of breathing (VO2 resp) and lung volume at constant load, ventilation, work rate, and pressure-time product in five trained normal subjects breathing through an inspiratory resistance at functional residual capacity (FRC) and when lung volume (VL) was increased to 37 +/- 2% (mean +/- SE) of inspiratory capacity (high VL). High VL was maintained using continuous positive airway pressure of 9 +/- 2 cmH2O and with the subjects coached to relax during expiration to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 0 publications
3
23
1
Order By: Relevance
“…7 Furthermore, any reduction of intrinsic PEEP with COPD results in a marginal deflating effect, and the reductions in effort of breathing may occur at the expense of increases in end-expiratory lung volume, which may aggravate the hyperinflation, 7 which in turn limits the ability of the diaphragm to increase lung volume 8 and increases oxygen cost of breathing during resistive breathing. 9 It is noteworthy that our best cutoff of 2.45 cm is close to the 2.6-cm cutoff of Reich et al, 15 who found that a right diaphragmatic arc height of Յ 2.6 cm identified 68% of subjects with abnormal pulmonary function tests, suggesting COPD. Although other radiographic parameters such as lung length and retrosternal lucency are also correlated with a COPD diagnosis, we chose the height of the right diaphragmatic arc based on the results of Reich et al, 15 the greater dependence of other parameters (such as lung length) on the subject's morphometry (such as height), and studies showing diaphragm flattening as having a better correlation with postmortem changes in emphysema.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…7 Furthermore, any reduction of intrinsic PEEP with COPD results in a marginal deflating effect, and the reductions in effort of breathing may occur at the expense of increases in end-expiratory lung volume, which may aggravate the hyperinflation, 7 which in turn limits the ability of the diaphragm to increase lung volume 8 and increases oxygen cost of breathing during resistive breathing. 9 It is noteworthy that our best cutoff of 2.45 cm is close to the 2.6-cm cutoff of Reich et al, 15 who found that a right diaphragmatic arc height of Յ 2.6 cm identified 68% of subjects with abnormal pulmonary function tests, suggesting COPD. Although other radiographic parameters such as lung length and retrosternal lucency are also correlated with a COPD diagnosis, we chose the height of the right diaphragmatic arc based on the results of Reich et al, 15 the greater dependence of other parameters (such as lung length) on the subject's morphometry (such as height), and studies showing diaphragm flattening as having a better correlation with postmortem changes in emphysema.…”
Section: Discussionsupporting
confidence: 76%
“…For instance, hyperinflation limits the ability of the diaphragm to increase lung volume 8 and can further increase the oxygen cost of breathing during resistive breathing. 9 These considerations are of particular relevance in the overlap syndrome, in which PAP, as indicated for sleep apnea, may be met with the same adherence issues as with NIV in COPD. Accordingly, patients with the overlap syndrome provide a unique opportunity to assess determinants of adherence to PAP therapy in COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Similar arguments may account for the smaller critical Pdi, if the diaphragm operates at shorter lengths during acute hyperinflation, when a given force requires much greater excitation [25]. At half inspiratory capacity, E can be reduced by as much as 50% [26]. To our knowledge, the efficiency of respiratory muscles has never been measured in patients who fail to wean.…”
Section: Increased Energy Demandsmentioning
confidence: 91%
“…] resistance (37,98,106,117). The increase in ERV has the effect of increasing internal respiratory load by raising the elastic lung load (14), which allows more passive expiration but results in a requirement for higher negative inspiratory pressures (76). The increased elastic load induced by immersion augments the gas density-related decrease in MVV (129).…”
Section: Respiratory Mechanicsmentioning
confidence: 99%
“…The increased work of breathing with negative P TR can be attributed to an increase in internal respiratory resistance due to compression of the extrathoracic airways (2). Positive P TR causes subjects to have a higher expiratory reserve volume and increased elastic recoil of the lungs (14). However, several studies have shown that the increased work of breathing caused by changes in P TR between ϩ10 and Ϫ20 cmH 2 O during exercise can cause dyspnea but does not translate into higher PET CO 2 (40,75,107), although in these studies it is possible that Pa CO 2 was underestimated by PET CO 2 .…”
mentioning
confidence: 99%